Segmenting Hedonic Wine Tourists Using Push–Pull Winescape Attributes - Quintal, Vanessa; Thomas, Ben; Phau, Ian; Soldat, Z. (2021)
The present research addresses the push–pull winescape traits of the hedonic wine tourism segment and discusses their attitudinal and behavioral intentions. The self-governing pen-and-paper survey conveniently sampled 301 wine tourists in situ at the Swan Valley winery in Western Australia. Push–pull winescape qualities generated a segmentation basis for cluster analysis, which defined four divisions—Inspireds, Self-Drivens, Market-Drivens, and Inerts. Inspireds exhibited the most favorable attitude toward the winery and were the most willing to recommend the winery, whereas Inerts demonstrated the converse effect. Theoretically, the segmentation bases, building on the Push–Pull winescape properties, provide a fresh and more nuanced description of the wine tourism categories in Australia’s rising wine tourism sector. Idealistically, this new image is important in delivering marketing insights to fewer Australian wine producers whose only connection to regional retail and export markets is via direct sales at the winery gates.